2012
DOI: 10.7567/jjap.52.010205
|View full text |Cite
|
Sign up to set email alerts
|

Toward Online Nanoscale Diffusion Measurements Using Radioactive 8Li Tracer

Abstract: We have examined the feasibility of a new online nanoscale diffusion measurement method using a radioactive 8Li tracer by computer simulations. We have found that the detection limit of the lithium diffusion coefficient can be improved to a low value of 1×10-12 cm2/s by detecting α particles emitted at a small angle relative to a sample surface that is irradiated with a low-energy 8Li beam of about 8 keV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the present case, however, the inherent energy distribution of the a particles is continuous and broad [7]. Although the correspondence between the emitted position and measured energy of the charged particles is not as simple as above-mentioned, it was shown that the tracer diffusion coefficient could be obtained from the time-dependent yields of a particles emitted by diffusing 8 Li with the help of the simulation [8][9][10]. Fig.…”
Section: Measurement Of LI Diffusion Length From Micrometer To Nanomementioning
confidence: 62%
See 4 more Smart Citations
“…In the present case, however, the inherent energy distribution of the a particles is continuous and broad [7]. Although the correspondence between the emitted position and measured energy of the charged particles is not as simple as above-mentioned, it was shown that the tracer diffusion coefficient could be obtained from the time-dependent yields of a particles emitted by diffusing 8 Li with the help of the simulation [8][9][10]. Fig.…”
Section: Measurement Of LI Diffusion Length From Micrometer To Nanomementioning
confidence: 62%
“…deviation of the values of ''Ratios'' from the constant value of ''1'', were observed by a shallow implantation depth even at the lower temperature than observed by a deep implantation depth (LVSO-523K). The solid line results from the simulation with a diffusion coefficient best reproducing the experimental spectra[10].…”
mentioning
confidence: 72%
See 3 more Smart Citations